Investigasi Lingkungan Termal Ruang Kelas Sekolah di Kota Pontianak - Lestari Lestari; Muhammad Ridha Alhamdani; Muhammad Nurhamsyah; Syaiful Muazir; Rudiyono Rudiyono (Universitas Sebelas Maret Surakarta, 2022)
The research of the thermal environment of the school building is useful for determining the design strategy of a thermally comfortable school building. This research method is based on field measurements. A total of 8 classrooms from 4 public school buildings in Pontianak City with different characteristics of opening directions, orientations, and floor locations were selected in this study. The results showed that the air temperature and humidity in the classroom ranged between 26.9oC-33.5oC and 74.5%-84.2%. The average air velocity in the classroom is 0.24m/s. The globe temperature is higher than the air temperature with an average difference of 7.7oC. Protection against solar radiation and increased air velocity can be potential design strategies to achieve thermal comfort in classrooms.